Analysis of Workaholism and Burnout Among Employees of Administrative Units and Two Selected Banks in Slovenia - Tatjana Kozjek; Anja Bandelj (Central European Public Administration Review)
Purpose: Workaholism and burnout can have detrimental effects on both employees and organisations in both the private and public sectors, and therefore calls for further research. The objective of this survey was to statistically analyse significant differences in the variables of workaholism and burnout (including emotional exhaustion, depersonalisation, and personal efficiency) between administrative units and two selected banks, among participants employed in managerial and non-managerial positions, and across genders. Additionally, the survey aimed to analyse the correlations between workaholism, emotional exhaustion, depersonalisation, and personal efficiency. The research involved 621 employees from 58 administrative units and 404 employees from two selected (private) banks in Slovenia. Design/Methodology/Approach: Various methodological approaches were used, including statistical tests such as multivariate and factor analysis, the Kolmogorov-Smirnov and Shapiro-Wilk tests, the Mann-Whitney U test, and Spearman’s rank-order correlation coefficient. Findings: Survey results revealed no statistically significant differences in the variables of workaholism and burnout between administrative units and the two selected banks, among participants employed in managerial and non-managerial positions, and across genders. However, the research uncovered a strong positive correlation between workaholism and emotional exhaustion, a weak positive correlation between workaholism and depersonalisation, and a slight negative correlation between workaholism and personal efficiency. Originality/Value: The research contributes to the growing awareness of workaholism and burnout, offering organisations valuable insights to address these issues and enhance employee well-being. Furthermore, it adds to the existing literature on workaholism and burnout within the context of Slovenia.